CNT/DFNS nanoparticles as a valuable admixture for ultrahigh-performance concrete - Seyed Alireza Nasabolhosseini; Amin Honarbakhsh; Rahele Zhiani; Seyed Mojtaba Movahedifar; Mehdi Nobahari (Results in Engineering)
Effective dispersion of carbon nanotubes (CNTs) is essential for optimizing low water-to-binder concrete mixtures. At higher concentrations, dispersing CNTs becomes highly challenging with standard plasticizers. This study investigates the production of concrete incorporating CNT/DFNS and CNTs particles with a grafted layer of dendritic fibrous nano-silica (DFNS) on their surface. Concrete, selected as an ideal low water-to-binder mix with high silica fume content, demonstrated that all CNT/DFNS samples reduced viscosity, extended workability, and required less mixing power than concrete with only CNTs. Notably, CNT/DFNS also significantly lowered the need for polycarboxylate superplasticizer for effective dispersion. Additionally, concrete with CNT/DFNS exhibited an 18 % increase in compressive strength compared to CNTs-only concrete. Scanning electron microscopy confirmed that CNT/DFNS achieved superior dispersion within the concrete matrix. Given their reduced viscosity, enhanced workability, decreased energy needs, and improved strength, CNT/DFNS show promising potential to advance concrete manufacturing. This marks the first instance of covalently bonding microporous DFNS to CNTs for concrete production. This breakthrough allows for the simple fabrication of ultra-high-performance concretes with outstanding strength and workability, showcasing the significant potential of self-dispersible DFNS and CNTs in cutting-edge concrete technologies.